Role of Dendritic Cell Maturity/Costimulation for Generation, Homeostasis, and Suppressive Activity of Regulatory T Cells - Pletinckx, Katrien; Döhler, Anja; Pavlovic, Vladimir; Lutz, Manfred B. (Frontiers in Immunology, 2011)
Tolerogenicity of dendritic cells (DCs) has initially been attributed exclusively to immature/resting stages, while mature/activated DCs were considered strictly immunogenic. Later, all different subsets among the myeloid/conventional DCs and plasmacytoid DCs have been shown to bear tolerogenic potential, so that tolerogenicity could not be attributed to a specific subset. Immunosuppressive treatments of immature DC subsets could prevent re-progamming into mature DCs or up-regulated inhibitory surface markers or cytokines. Furthermore, the different T cell tolerance mechanisms anergy, deletion, immune deviation and suppression require different quantities and qualities of costimulation by DCs. Since expansion of regulatory T cells (Tregs) has been shown to be promoted best by fully mature DCs the role of CD80/B7-1 and CD86/B7-2 as major costimulatory molecules for Treg biology is under debate. In this review, we will discuss the role of these and other costimulatory molecules on myeloid DCs and their ligands CD28 and CD152/CTLA-4 on Tregs for peripheral conversion from naive CD4+ T cells into the major subsets of Foxp3+ Tregs and Foxp3- IL-10+ regulatory type-1 T cells (Tr1) or Tr1-like cells and their role for peripheral maintenance in the steady state and after activation.